The Effect of Leverage and Profitability on the Integrity of Financial Statements with Moderation of Audit Quality - Alpriyatna, Ricky; Muhyarsyah , Muhyarsyah (Green Publisher Indonesia, 2023)
Today's industrial revolution 4.0 requires companies to interact directly with the global market. The intense global competition that we face includes the rapidly growing economy accompanied by technological developments. The purpose of this research is to examine several aspects that affect the integrity of financial statements. The data analysis technique used is multiple linear regression analysis. The population is companies registered on the IDX. The data was collected using a purposive sampling method, with a sample size of 75 samples. The independent variables of this research are Profitability and Leverage. the dependent variable of this research is the integrity of financial reporting. The research findings prove that the variables of Profitability, and Leverage do not have an impact on Financial Statement Integrity in all categories of this research, while Profitability is able to moderate the influence on Financial Statement Integrity.